Factor Affect Motivation in Research Working of Personal Rajamangala University of Technology Lanna Phitsanulok Campus - Rangkhing, Rutchaneekong; Naku, Arporn; Potikhambumrung, Patikamol (RMUTL Journal of Business Administration and Liberal Arts, 2017)
This research aims to study effects of intrinsic and extrinsic motivation of personnel at Rajamangala University of Technology Lanna, Phitsanulok Campus, on conducting research, as well as to compare motivation level according to personal variables.Samples in this research consisted of 124 working personnel in academic year 2015. A tool used in this research was a 40-item 5-point rating scale questionnaire, with reliability level of 0.966. Statistics used for data analysis included percentage, mean, standard deviation, t-test for two-group comparison, and one way ANOVA. The research yielded the following results: 1) Overall motivation level of personnel in conducting research was in middle level. The personnel had high level of intrinsic motivation, but middle level of extrinsic motivation for conducting research. 2) Intrinsic motivations that had the highest effect on conducting research were promotion in work, the extrinsic motivations that had the highest effect on conducting research were modern technology.3) Female personnel had higher level of motivation in conducting research than male personnel at a significant level of 0.01 and 4) Personnel with different age, educational level, working period, and position did not have significant difference in motivation to conduct research.